Performance of cyclical sectors on the klse - Poobalan, S / O Tana Shingam (Universiti Malaysia Sarawak, (UNIMAS), 2002)
This study attempts to examine the relationship between the stock market, ri and returns before, during and after crisis for the period from 1995 to 2000 t0 cyclical and non-cyclical sectors in Malaysia. The Kuala Lumpur Stock Exchange Composite Index (KLSE CI)represents the stock market, risks (in % and the returns (in %)